Public choice for payment vehicles of turtle conservation in Terengganu, Malaysia - MAHIRAH KAMALUDIN; ROSELIZA MAT ALIPIAH; NIK SALBIAH NIK NORDIN; NURAIN AFIQAH (Society for Indonesian Biodiversity, 2023)
Abstract. Kamaludin M, Alipiah RM, Nordin NSN, Afiqah N. 2023. Public choice for payment vehicles of turtle conservation in Terengganu, Malaysia. Biodiversitas 24: 636-644. Sea turtle is known as the iconic natural heritage in Terengganu, Malaysia. Unfortunately, the turtle populations are declining these days due to many threats such as incidental catch, human activities, coastal development, irresponsible tourism, and poaching. Besides, erosion occurs on some beaches, reducing the area available for turtle nesting. This study determines marginal willingness to pay (WTP) for sea turtle conservation programs with two different payment vehicles i.e. tax collection and trust fund in Terengganu, Malaysia. The choice experiment (CE) method was utilized to calculate the marginal WTP of four attributes (population of sea turtles, communities involved, conservation activities and tax/trust fund). The study found that public placed a higher value of the marginal WTP on the ‘conservation activities’ attribute with RM3.32 (tax) and RM110.11 (trust fund), while the public exhibited higher values of WTP on the medium of payment vehicle (trust fund), where the coercive payment was not favorable among them. Therefore, a workable and suitable medium of payment is essential to support the efforts in protecting sea turtles and keeping coral reefs and sea grass beds healthy. After all, more sea turtles will survive and thrive to maintain the fragility of ecosystem's balance in the ocean.